2015
DOI: 10.1039/c5cp05442g
|View full text |Cite
|
Sign up to set email alerts
|

Energy levels in CaWO4:Tb3+at high pressure

Abstract: The luminescence properties of Tb(3+) in CaWO4 crystals are investigated under a hydrostatic pressure of up to 200 kbar, i.e. across scheelite-to-fergusonite phase transition. It is shown that the typical blue ((5)D3) and green ((5)D4) emissions in this material are progressively quenched at room temperature as pressure is increased. This quenching is caused by a downshift of the charge transfer (or impurity trapped exciton) state that is formed between Tb(3+) and nearby W(6+) cations in conjunction with a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…For scheelite-type ZrGeO 4 (space group: I4 1 /a), according to the group theory analysis, 13 Raman active modes are predicted: 3A g + 5B g + 5E g . In agreement with the previous report, all 13 expected Raman modes are detected, as shown in Figure 2 with the symmetry assignment summarized in Table 1. 25 Out of these 13 Raman active modes, 7 are internal modes originated from GeO 4 tetrahedra.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…For scheelite-type ZrGeO 4 (space group: I4 1 /a), according to the group theory analysis, 13 Raman active modes are predicted: 3A g + 5B g + 5E g . In agreement with the previous report, all 13 expected Raman modes are detected, as shown in Figure 2 with the symmetry assignment summarized in Table 1. 25 Out of these 13 Raman active modes, 7 are internal modes originated from GeO 4 tetrahedra.…”
Section: Resultssupporting
confidence: 92%
“…Several experiments and theoretical results have confirmed that the scheelite- and zircon-type compounds are rather sensitive to the external pressure, and pressure-induced phase transitions usually occur for these compounds during compression . For instance, scheelite-to-fergusonite phase transition for CaWO 4 , a typical scheelite-type material, has been confirmed at around 10.0 GPa under quasi-hydrostatic conditions. The pressure induced phase transition from the zircon to scheelite structure has also been observed for the typical zircon structure material ZrSiO 4 . , Many other scheelite- and zircon-structured ABO 4 ternary oxides have also been extensively studied, and similar results were reported for other ABO 4 materials, including tungstates, molybdates, vanadates, and phosphates. …”
Section: Introductionmentioning
confidence: 84%
“…This method has been used to estimate the location of the ground states of Tb 3+ and Pr 3+ with respect to conduction band in many materials. [14][15][16][17][18][19][20][21][22][23][24] We have chosen Y 2 O 2 S doped with Eu 3+ and Y 2 O 2 S doped with Tb 3+ to demonstrate how high-pressure spectroscopy can be used to determine the energetic structures of dielectric hosts doped with Ln 3+ and Ln 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…We therefore estimate that both CT processes contribute to the edge of the excitation spectrum recorded at ambient pressure. Following the arguments developed recently in ref , we estimate the action of pressure on the Bi–V CT energy as follows: where d P expresses the pressure dependence of the Bi–V distance in YVO 4 –Bi 3+ . This parameter can be calculated from eq , incorporating in this equation a pressure-induced collapse of the Y–V distance of −0.0055 Å/GPa, as deduced from ref .…”
Section: Results and Discussionmentioning
confidence: 99%